Building Future-Ready Economic Education Students at UNESA: Internship, Self-Efficacy, and Resilience in Supporting SDG 4 for Quality Education - Anandita Alifya Hardiyani; Abdullah Azzam Robbani; Arina Salsabilla Haq (Journal of Psychology and Culture Behavior in SDGs, 2025)
Objective: This study investigates the influence of internship experiences and self-efficacy on the resilience of Economics Education students at Surabaya State University (UNESA), covering four study programs: Economics Education, Business Education, Accounting Education, and Office Administration Education. Method: A quantitative approach was employed, involving 173 students selected through proportionate random sampling. Instrument feasibility testing was conducted prior to questionnaire distribution using IBM SPSS 25 to assess validity and reliability. Data analysis was performed using Structural Equation Modeling (SEM) with WarpPLS 8.0. The evaluation included outer model analysis (validity and reliability), inner model analysis (path coefficients and relationships among constructs), and model fit testing (Goodness of Fit). Results: The findings reveal that internship experiences significantly enhance both self-efficacy and resilience, with self-efficacy serving as a partial mediator between the two. The most influential factors in strengthening resilience were perceived control and collaborative success during the internship. Furthermore, internships were found to contribute directly to career preparation, as students gained confidence in classroom management, adaptability, and pedagogical skills while simultaneously developing a stronger professional identity. This resilience was closely tied to the formation of professional identity, which in turn supported career readiness and increased motivation for long-term commitment to the teaching profession, thereby enhancing career retention. These results extend Bandura’s self-efficacy theory by showing how psychological resilience and professional identity together foster readiness for the demands of teaching. Novelty: The novelty of this research lies in integrating internship, self-efficacy, and resilience into a single PLS-based structural model in the context of teacher education, a comprehensive approach rarely addressed in prior studies. Theoretically, this study enriches educational psychology by highlighting the role of self-efficacy and resilience in shaping professional identity and retention. Practically, it contributes to developing effective internship strategies that prepare future teachers to be academically competent, psychologically resilient, and professionally committed. This study strongly supports SDG 4 (Quality Education) by emphasizing the importance of high-quality teacher education that builds not only technical competencies but also resilience, adaptability, and sustained professional engagement.